DEVELOPING SPEAKING SKILLS OF STUDENTS THROUGH CLIL (CONTENT LANGUAGE AND INTEGRATED LEARNING) - Orzikulova Mavsuma Mamatkulovna,; Ravshanova Madinabonu G’ulom qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The notion of Content and Language Integrated Learning (CLIL) is the focus of this article, which also examines a number of extremely successful classroom activities for teaching English. CLIL is a cutting-edge method of teaching that combines language learning with subject matter, enabling pupils to pick up both language and knowledge at the same time. The study emphasizes the use of CLIL-based exercises in English lessons to foster a more dynamic, interesting, and relevant learning environment.The paper also looks at how CLIL helps students develop their cognitive, communication, and teamwork skills. Learners are taught to think critically, solve issues, and communicate their ideas in the target language through thoughtfully crafted exercises. This dual-focused strategy promotes the growth of subject-specific knowledge in addition to improving language skills.